Assessment of laboratory test request forms for completeness - Udeh, Chioma; Olayanju, Olatunde; Awah, Nnaemeka; Bamidele, Olabisi; Eseile, Bola; Okwonkwo, Onyinye; Odok, Gabriel (International Journal of Medicine, 2021)
Background: Laboratory test request forms usually accompany patientâ€™s samples to the laboratory, providing biodata and clinical details of the patient. This information is for purposes of identification and guiding pathologists to accurately interpret patientâ€™s result. Clinicians however do not usually provide all the required information, thus making interpretation difficult. The frequency of such incompleteness is assessed in this study.Methods: Laboratory request forms received at the Chemical Pathology laboratory between July and September 2020 were assessed for completeness of all the required parameters. Parameters analyzed in this study included age, gender, hospital number, location, clinical information, name of requesting physician and the date of request. Frequency of missing parameters were expressed as proportions (%) of the total omissions.Results: There were 1906 request forms received during the course of this study and 789 (41.4%) of them had at least one missing parameter. Apart from patientsâ€™ names, nature of sample and the requested investigation, all other parameters were omitted at one time or the other making a total of 1117 omissions. Age (287; 25.7%) hospital number (264; 23.6%) and clinical information (246; 22%) were the most commonly omitted parameters. Majority of the omissions (69%) were from the outpatient clinics, 20% were from the wards while 10% of the forms had no ward or clinic indicated.Conclusion: Incomplete filling of laboratory test request forms is a regular occurrence among clinicians. Effort must be made to continually sensitize them of the importance of each of the required parameters to ensure a visible improvement.Â Â